Das "Augsburger Sakramentar": Clm 30040 (olim Donaueschingen 193) : Entstehungsort und Datierung - Berschin, Walter (Revue bénédictine, 2020)
München, Bayerische Staatsbibliothek Clm 30040 (olim Donaueschingen 193), a Sacramentary designed on a grand scale and decorated in gold, has tentatively been dated and localized variously. A close examination of the script and contents of this splendid book shows that it belongs into a group of late Reichenau manuscripts. The Sacramentary was written around 1060 for the cathedral of Augsburg and commissioned probably by bishop Heinrich II. of Augsburg (1047-1063).